Development of Multi-EAP Radius Configuration for eduroam Service - Petrosyan, Arthur S.; Petrosyan, Gurgen S.; Tadevosyan, Robert N.; Arsalanian, Kevork Kh. (Mathematical Problems of Computer Science, 2021)
This paper describes the mechanism of authenticating multiple-realm eduroam users via a single multi-EAP radius configuration. The solution is based on the fact that some organizations, which are willing to join the eduroam community and use the service, especially in small communities, do not have a huge number of users, thus it will be costeffective to use a single RADIUS server for them instead of having a separate radius server per each realm. The solution is unmatched in terms of practical open implementation. It has been implemented and tested in ASNET-AM network.